2018
DOI: 10.31486/toj.18.0005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Component Alignment in Total Knee Arthroplasty

Abstract: Background: Obesity is routinely cited as a negative predictive factor for outcomes after total knee arthroplasty (TKA), but the direct mechanism responsible for this relationship has not been described. One possible explanation is a propensity for component malalignment in obese patients that is attributable to difficulty with surgical exposure. Methods: This study evaluated the effect of obesity on TKA component alignment in 251 primary TKAs during a 12-month period at a single center in 2009. Postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This study demonstrated that obese and morbidly obese patients were younger at time of index TKA, possibly due to earlier onset and accelerated progression of osteoarthritis 4,15,17,39,55,59,60,66,71,82,87 . This is likely to be contributed by increased stresses acting on the articular surfaces secondary to higher body weight, leading to osteoarthritis development 2 .…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…This study demonstrated that obese and morbidly obese patients were younger at time of index TKA, possibly due to earlier onset and accelerated progression of osteoarthritis 4,15,17,39,55,59,60,66,71,82,87 . This is likely to be contributed by increased stresses acting on the articular surfaces secondary to higher body weight, leading to osteoarthritis development 2 .…”
Section: Discussionmentioning
confidence: 75%
“…One additional article was identified from citation search and 210 full‐text articles were assessed for eligibility. Finally, 91 studies were included, with 22 prospective, 4,7,8,16,22–39 54 retrospective, 6,9–12,14,15,17,40–85 and 15 case‐controlled studies 5,13,18,19,86–96 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While some authors have reported greater risk for limb malalignment in TKAs when performed in the obese, 1,2 others have shown no increase in risk for mal-alignment in the obese patients undergoing TKA. 3,4 Similarly, some studies have showed comparable clinical and functional results between obese and non-obese patients 4e6 and others have concluded obesity to have a negative influence on the clinical and functional outcome after TKA. 7e9 Over the years, studies have established the superiority of computer-assisted TKA in achieving the desired component and limb alignment in comparison to that achieved by conventional TKA.…”
Section: Introductionmentioning
confidence: 98%